2020
DOI: 10.1007/s00464-020-07429-3
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic common bile duct exploration in patients with previous abdominal biliary tract operations

Abstract: Background A history of abdominal biliary tract surgery has been identified as a relative contraindication for laparoscopic common bile duct exploration (LCBDE), and there are very few reports about laparoscopic procedures in patients with a history of abdominal biliary tract surgery. Methods We retrospectively reviewed the clinical outcomes of 227 consecutive patients with previous abdominal biliary tract operations at our institution between December 2013 and June 2019. A total of 110 consecutive patients un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(34 citation statements)
references
References 30 publications
1
33
0
Order By: Relevance
“…19 However, there are few reports of surgical outcomes comparing LCBDE with OCBDE in patients with a history of prior biliary surgery. 20 In the present study, 162 patients with previous biliary operation had undergone reoperation, 72 of them were laparoscopic approach, and the remaining 90 were open surgery. The stone clearance rate in the LCBDE group and OCBDE groups were 97.2% and 96.7%, respectively, and there was no statistical significance between the two groups.…”
Section: Discussionmentioning
confidence: 77%
See 4 more Smart Citations
“…19 However, there are few reports of surgical outcomes comparing LCBDE with OCBDE in patients with a history of prior biliary surgery. 20 In the present study, 162 patients with previous biliary operation had undergone reoperation, 72 of them were laparoscopic approach, and the remaining 90 were open surgery. The stone clearance rate in the LCBDE group and OCBDE groups were 97.2% and 96.7%, respectively, and there was no statistical significance between the two groups.…”
Section: Discussionmentioning
confidence: 77%
“…[11][12][13][14] With the development of laparoscopic equipment and technology, there are a few studies have reported data on the application of LCBDE to patients after cholecystectomy and/or common bile duct exploration. [16][17][18][19][20] For all that, LCBDE has not been widely employed due to the technical challenge for CBDS in those patients. It is still unknown whether LCBDE is as feasible and safe as OCBDE for CBDS in patients with a history of prior biliary surgery.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations